Near Infrared‐Triggered Theranostic Nanoplatform with Controlled Release of HSP90 Inhibitor for Synergistic Mild Photothermal and Enhanced Nanocatalytic Therapy with Hypoxia Relief. Issue 28 (6th June 2022) - Tian, Boshi; Wang, Chen; Du, Yaqian; Dong, Shuming; Feng, Lili; Liu, Bin; Liu, Shikai; Ding, He; Gai, Shili; He, Fei; Yang, Piaoping
Abstract: Mild photothermal therapy (PTT, <45 °C) can prevent tumor metastasis and heat damage to normal tissue, compared with traditional PTT (>50 °C). However, its therapeutic efficacy is limited owing to the hypoxic tumor environment and tumor thermoresistance owing to the overproduction of heat shock proteins (HSPs). Herein, a near‐infrared (NIR)‐triggered theranostic nanoplatform (GA‐PB@MONs@LA) is designed for synergistic mild PTT and enhanced Fenton nanocatalytic therapy against hypoxic tumors. The nanoplatform is fabricated by the confined formation of Prussian blue (PB) nanoparticles in mesoporous organosilica nanoparticles (MONs), followed by the loading of gambogic acid (GA), an HSP90 inhibitor, and coating with thermo‐sensitive lauric acid (LA). Upon NIR irradiation, the photothermal effect (44 °C) of PB not only induces apoptosis of tumor cells but also triggers the on‐demand release of GA, inhibiting the production of HSP90. Moreover, the delivered heat simultaneously enhances the catalase‐like and Fenton activity of PB@MONs@LA in an acidic tumor microenvironment, relieving the tumor hypoxia and promoting the generation of highly toxic OH. In addition, the nanoplatform enables magnetic resonance/photoacoustic dual‐modal imaging. Thus, this study describes a distinctive paradigm for the development of NIR‐triggered theranostic nanoplatforms for enhanced cancer therapy. Abstract : A near‐infrared (NIR)‐triggered nanoplatform with controlled release of an heat shock proteins (HSPs) inhibitor for synergistic mild photothermal and enhanced Fenton nanocatalysis is developed. Upon NIR irradiation, gambogic acid is released and inhibits the expression of HSP90. Notably, the nanoplatform simultaneously relieves the tumor hypoxia and enhances the efficacy of the nanocatalytic therapy in an acid tumor microenvironment.